Training ESL students to reproduce beat gestures in discourse leads to L2 pronunciation improvements - Prieto, Pilar; Kushch, Olga; Borràs-Comes, Joan; Gluhareva, Daria; Pérez-Vidal, Carmen (Anuario del Seminario de Filología Vasca "Julio de Urquijo.", 2025)
The main goal of the present study is to assess whether training foreign language students to reproduce natural beat gestures in discourse can trigger pronunciation gains. A total of 18 young adult Catalan learners of English with an intermediate proficiency level participated in a 15-minute discourse-based pronunciation training session. Participants were randomly assigned to two groups. While one group was asked to simply repeat the instructor’s multimodal responses to discourse prompts by focusing on speech, the other group was asked to repeat the utterances together with the natural beat gestures that the instructor was using. Before and after training, participants were recorded producing a discourse completion task and their speech was rated for accentedness. Results showed that participants who accompanied their verbal repetition with beat gestures during training significantly reduced their accentedness scores more than those who were asked to only repeat the utterances without reproducing the beat gestures. These results support recent findings that show the value of embodied prosodic training for pronunciation instruction.